Polyploidy in Fruit Tree Crops of the Genus Annona (Annonaceae) - Martin, Carolina; Viruel, Maria. A.; Lora, Jorge; Hormaza, José I. (Frontiers in Plant Science, 2019)
Genome duplication or polyploidy is one of the main factors of speciation in plants. It is especially frequent in hybrids and very valuable in many crops. The genus Annona belongs to the Annonaceae, a family that includes several fruit tree crops, such as cherimoya (Annona cherimola), sugar apple (Annona squamosa), their hybrid atemoya (A. cherimola × A. squamosa) or pawpaw (Asimina triloba). In this work, genome content was evaluated in several Annona species, A. triloba and atemoya. Surprisingly, while the hybrid atemoya has been reported as diploid, flow cytometry analysis of a progeny obtained from an interspecific cross between A. cherimola and A. squamosa showed an unusual ploidy variability that was also confirmed karyotype analysis. While the progeny from intraspecific crosses of A. cherimola showed polyploid genotypes that ranged from 2.5 to 33%, the hybrid atemoyas from the interspecific cross showed 35% of triploids from a total of 186 genotypes analyzed. With the aim of understanding the possible implications of the production of non-reduced gametes, pollen performance, pollen size and frequency distribution of pollen grains was quantified in the progeny of this cross and the parents. A large polymorphism in pollen grain size was found within the interspecific progeny with higher production of unreduced pollen in triploids (38%) than in diploids (29%). Moreover, using PCR amplification of selected microsatellite loci, while 13.7% of the pollen grains from the diploids showed two alleles, 41.28% of the grains from the triploids amplified two alleles and 5.63% showed up to three alleles. This suggests that the larger pollen grains could correspond to diploid and, in a lower frequency, to triploid pollen. Pollen performance was also affected with lower pollen germination in the hybrid triploids than in both diploid parents. The results confirm a higher percentage of polyploids in the interspecific cross, affecting pollen grain size and pollen performance. The occurrence of unreduced gametes in A. cherimola, A. squamosa and their interspecific progeny that may result in abnormalities of ploidy such as the triploids and tetraploids observed in this study, opens an interesting opportunity to study polyploidy in Annonaceae.